Economic growth : fiftieth annniversary colloquium 5 (New York: National Bureau of Economic Research; distributed by Columbia University Press, 1972)
Contains the proceedings of the Economic Growth Colloquium, which was held at the Bank of America Centre in San Francisco, California, on December 10, 1970.
Includes bibliographical references.
oif 30/01/2019
Ref.
Keywords: Economic development; United States